Determinants of earnings persistence in Indonesian food and beverage firms - Juli Ismanto; Effriyanti Effriyanti; Lioni Indrayani (Indonesia Accounting Research Journal, 2026)
There has been a great deal of mixed empirical evidence on the determinants of earnings persistence, largely because previous research has looked at individual variables in isolation rather than within a comprehensive framework. Also, there is no evidence from non-cyclical industries in the wake of the post-pandemic recovery. This research aims to examine the joint effect of operating cash flow, tax planning strategies and debt levels on earnings persistence of Indonesian food and beverage companies listed on the Indonesia Stock Exchange in the period 2020-2024. This study adopted a quantitative approach using secondary data from 21 firms, providing 105 firm-year observations. Panel data regression analysis with the fixed-effects model was employed to test the hypotheses in the study. The results show that cash flow from operation has positive effect on earnings persistence (β = 0.254, p = 0.015) and tax planning has the most positive effect (β = 0.500, p = 0.014). Conversely, debt levels do not have a statistically significant impact (β = 0.002, p = 0.988) and the model explains 71.5% of the variance in earnings persistence (adjusted R² = 0.715). This study provides a wide analytical framework that shows that operational efficiency and fiscal prudence are more important drivers of earnings quality in industries with stable demand than decisions about capital structure. The results challenge the generalisability of the debt monitoring hypothesis and point to operational transparency as an alternative to debt-based governance mechanisms in sectors that are insulated from the economic cycle.